The Effects of Age, Biological Maturation and Sex on the Development of Executive Functions in Adolescents - Laureys, Felien; Middelbos, Lotte; Rommers, Nikki; De Waelle, Silke; Coppens, Eline; Mostaert, Mireille; Deconinck, Frederik J. A.; Lenoir, Matthieu (Frontiers in Physiology, 2021)
The development of executive functions (EF) has gained increased attention in scientific literature and has been associated with expertise in many human activity domains, such as academic achievement and sports performance. The development of EF is assumed to be affected by multiple factors, among them biological maturation. Currently the association between biological maturation and EF is largely unexplored, in contrast to other domains like physical development or sports performance. Therefore, this study aimed a) to explore the effect of age on EF performance and b) to investigate to what extent age-related changes found in EF are affected by biological maturation. To this end, EF performance and degree of maturity, indexed by percentage of predicted adult height (%PAH), of 90 adolescents (11-16 years old, 54% males) were monitored on three occasions in a time frame of 12 months. A Generalized Estimating Equation (GEE) approach was used to examine the association between chronological age and %PAH and the weighted sum scores for each EF component (i.e., inhibition, planning, working memory, shifting). All models also included the effect of sex. The results indicated that EF performance improved with age and degree of maturity on all four components. Interaction effects between age and %PAH on inhibition showed that at the start of puberty, early mature participants had a lower chance of performing well on inhibition, whereas later in puberty early mature participants had a higher chance to have a good inhibition performance. For working memory, it seems that there is no maturity effect at a younger age, while at a later stage in puberty, a disadvantage for late maturing peers compared to on-time and early maturing adolescents emerged. Sex also affected EF performance, with girls outperforming boys in planning and shifting while the opposite was found for inhibition. This study is one of the first to investigate the effect of biological maturation on EF performance, and shows that distinct components of EF are affected by maturational status. Further research is warranted to unravel the implications for maturation-driven effects on EF that might significantly affect domains of human functioning like academic achievement and social development.